Nothing compares to the duke - Carlyle, Christy (Carlyle, Christy. Duke's Den, 2020)
"Rhys Forester, the new Duke of Claremont, lives his life by four words: Enjoy All, Regret Nothing. He's devoted to the pleasure of his wild soirees, reckless behavior, and shocking the ton with his interests in trade. The debts that come with his title don't fit the carefree lifestyle he's created, and when he's forced to return to his family's estate, he's also forced to confront his one and only regret: the beautiful girl he left behind. Arabella Prescott has been the belle of more balls than she cares to remember. After three seasons and five rejected proposals, she's done with the marriage mart. Bella's hopes to live a comfortable life, alone, come crashing down when her parents demand she marry. But her salvation may come in the form of the man she hates the most. Bella has never forgiven Rhys for what he did to her, but desperate times call for fake engagements. With a few dozen rules, their scheme begins, but it's not long before the former enemies find themselves breaking every single rule, including the most important of them all: don't fall in love.--Provided by publisher.